Onset and offset of electromyographic (EMG) silence in asterixis. - Ugawa, Y (1990)
The onset and offset of electromyographic (EMG) silence were studied physiologically by silent period locked averaging method (SPLA) combined with a computer-assisted method for detecting EMG changes in 11 patients with asterixis of various aetiologies. The onset followed the EMG discharge which was closely associated with a sharp wave probably generated by the motor cortex in three patients. No EEG activity could be shown to be related to the offset of EMG silence in every patient. Jerky movement of asterixis was temporally related to the offset of EMG silence rather than the onset.